ANALISIS USABILITY PADA APLIKASI FLAVOUR FOG MENGGUNAKAN USE QUESTIONNAIRE - Albertus Marco Novellium Theovanus; Arfan Yunus; Ahyar Muawwal (KHARISMA Tech, 2023)
Flavour Fog is an android-based software specifically designed to make it easier for vape users to order and find information about vaping. This study aims to determine the usability value and the influence between the variables usefulness (usability), ease of use (ease of use), and ease of learning (ease of learning) on the satisfaction variable (user satisfaction) partially or simultaneously on Flavour Fog. In this study using the USE Questionnaire method with 4 parameters, namely usefulness, ease of use, ease of learning, and satisfaction. The result of the total percentage of feasibility of all variables based on usability measurements is 85%, which means it is very feasible. The results of the f test have a significant effect on the independent variable on the dependent variable simultaneously. In the partial T test, the results of the usefulness variable have a significant influence on the satisfaction variable, while the ease of use variable and the ease of learning variable have no effect on satisfaction.